Virtual robotic telepresence early childhood mental health consultation to childcare centers in the aftermath of COVID-19: training approaches and perceived acceptability and usefulness - Jent, Jason F.; St. George, Sara M.; Agosto, Yaray; Rothenberg, William A.; Howe, Elizabeth; Velasquez, Carolina; Mansoor, Elana; Garcia, Emperatriz G.; Bulotsky-Shearer, Rebecca J.; Natale, Ruby (Frontiers in Psychology, 2024)
Introduction Childcare center closures during COVID-19 impacted education for approximately 40 million children nationwide. Unfortunately, COVID-19 restrictions significantly limited the extent that outside personnel could provide in-person support to educators, resulting in the need for innovative approaches to meet childcare centers’ needs. A virtual robotic telepresence approach was applied to early childhood consultation models to promote child resilience while mitigating COVID-19 risks. The goal of this study was to examine how training influenced consultants’ and childcare staff uptake of the virtual robotic telepresence consultation approach and their acceptance of this technology. Methods Ten early childhood consultants received multimedia/simulation training and weekly communities of practice related to virtual telepresence robotic consultation. Telepresence robotic consultation equipment was deployed to 16 childcare centers in a diverse multilingual metropolitan area as a part of a larger randomized controlled trial. Consultants trained childcare staff (14 center directors and 58 teachers) on how to receive virtual telepresence robotic consultation. Demographic information and measures of technology acceptability and uptake were collected from childcare staff and consultants. A mixed methods approach was used including multilevel modeling and focus groups to examine consultation uptake, acceptability, barriers, and facilitators of virtual telepresence robotic consultation implementation. Results Consultants and childcare staff generally perceived the virtual telepresence consultation approach to be useful and easy to use. Consultant perceptions of the acceptability of technology did not change over time. Childcare staff, center, and consultant factors impacted the uptake of the virtual robotic telepresence consultation approach and childcare staff acceptance of the technology. Focus groups revealed that consultants believed that additional hands-on training with childcare staff would have benefited implementation and expressed a desire for a hybrid approach for consultation. Discussion Perceptions of telepresence robotic consultation acceptability are discussed, including future recommendations for training.